PENGARUH KOMUNIKASI, DISIPLIN KERJA DAN PENGAWASAN KERJA TERHADAP KINERJA KARYAWAN PT DOELLKEN BINTAN DI KOTA BATAM - Anshori, Muchammad Febri; Heryenzus (LPPM Universitas Putera Batam, 2022)
This study aims to determine and analyze the relationship of communication, work discipline and work supervision on the performance of employees of PT Doellken Bintan Batam. The research method used in quantitative research and data collection is done by using a questionnaire on a liquid scale. The samples used in this study were employees of PT Doellken Bintan with a total of 105 people. The results of the research show that partially communication has a positive and significant effect on employee performance, work discipline has a positive and significant influence on employee performance and work supervision has a positive and significant impact on employee performance of PT Doellken Bintan. Simultaneously, it was obtained that communication, work discipline and work supervision had a significant effect on the performance of PT Doellken Bintan employees. Based on the results of research conducted by researchers, suggestions that can be given to PT Doellken Bintan are the need for increased communication by all employees of PT Doellken Bintan both superiors, subordinates or co-workers, there is a need for increased supervision carried out by management to employees and the need for role models that must be given by the leadership to employees so that they can improve employee performance